Análise da paisagem por meio dos elementos físicos e socioeconômicos nos conjuntos habitacionais Alice Novack e Nilce Paes Barreto em Cuiabá - Dauar, Cláudia Maria Bernardes (2017)
This work aimed to understand the landscape from the space production process, in the scenario of the popular housing estates Alice Novack and Nilce Paes Barreto, in Cuiabá. And so, to study socioeconomic aspects and the relation of this landscape to the vegetation, one of the natural elements of this constructed environment, and that is the first one to be altered, in the molds, according to which, these enterprises are implanted. From this perspective, the specific objectives sought to raise if the vegetation is important for the resident of the housing complexes; To inquire whether the repetitive landscape, characteristic of the popular housing complexes, bothers; Identify problems caused by the peripheral location of popular housing; To reflect because, when they are implanted, these enterprises invariably provoke the devastation of the existing native vegetation, which is partly returned, in an insipient way at the end of the work; Relate vegetated environment and environmental quality in housing developments. For this purpose, supported by Tonetti and Nucci (2012, p.60), they propose methodological procedures to analyze the quality and distribution of trees planted on sidewalks and central beds, as a new criterion of the method for the determination of Urban Environmental Quality. The relevance of the research is to make it possible to discuss in the light of the geographical literature the presence of trees in the city and the benefits that the environment with vegetation brings to the environmental quality, above all, in the universe of the popular housing complexes, that at present have been the object of several studies And debates. In this way, the problem arose, considering that, as a rule, when building popular housing complexes, there is no concern on the part of the space-producing agents, represented here by the Builders and the Public Management of the urbanized landscape, afforestation, as well as the preservation of existing green areas. In this condition, supported by the Marxist perspective, which reveals the antagonisms and contradictions inherent in the process of production of urban space reflected in the environment and materialized in the landscape. The results were systematized in graphs and maps.